Multigeneration power: power generation from renewable source - Toh, Wee Kai (2022)
In recent years, solar-driven multigeneration systems have received a lot of attention due to their ability to produce multiple outputs from solar energy. Cogeneration and trigeneration systems are classified under the category of multigeneration systems. In this study, the cogeneration and trigeneration systems powered by solar energy had been proposed. Both systems utilize solar energy to generate electric power and hydrogen gas concurrently while the trigeneration system with an additional absorption chiller can produce an extra cooling capacity. The proposed systems were modelled in Aspen HYSYS to evaluate the overall performances of the systems. From the simulation results, it was found that when the direct normal irradiation (DNI) is 0.375 kW/m2 , both the cogeneration and trigeneration systems can generate 3 127.5 kW of electric power and 24.58 kg/h of hydrogen gas. The trigeneration system can produce an additional 54.97 kW of cooling capacity other than electric power and hydrogen gas. The efficiencies of the cogeneration and the trigeneration systems are 26.77% and 27.15% respectively. Other than performance evaluation, the life cycles of both systems were also assessed through GaBi software. Since both systems are driven by solar energy, the operations of the systems do not have direct impacts on the environment. However, the generation of electric power to drive the pumps in the systems as well as the processes of producing the working fluids for the systems bring some negative impacts to the environment. In 1 hour of operation, the global warming potential, acidification potential, and human toxicity potential of the cogeneration system are 145.4 kg of CO2-eq, 0.561 kg of SO2-eq, and 8.28 kg of 1,4-DCB-eq respectively. On the other hand, the operation of the trigeneration system has slightly higher environmental impacts compared to the cogeneration system due to the additional power and working fluid required by the absorption chiller. It was found that 145.937 kg of CO2-eq, 0.562 kg of SO2-eq, and 8.30 kg of 1,4-DCBeq will be emitted into the atmosphere when the trigeneration system operates for 1 hour.